2014 IEEE Conference on Technologies for Sustainability (SusTech) 2014
DOI: 10.1109/sustech.2014.7046238
|View full text |Cite
|
Sign up to set email alerts
|

Short-term load forecasting algorithm and optimization in smart grid operations and planning

Abstract: Electrical load forecasting is one of the important parts for smart grid system. The reliable prediction of the load demand contributes to the efficient and economical operations and planning. The artificial neural network is used extensively in load demand forecasting. The nonlinear nature of the electrical load demand conforms to the ability of the artificial neural network in calculating the nonlinear relationship of inputs and outputs. Among many models of neural networks, radial basis neural networks yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In paper [ 12 ], the author used an artificial neural network to predict short-term load because of the non-linear characteristics of ANN compared to other statistical models such as ARMAX, ARMA, regression, and Kalman filtering. Using MATLAB, he did a comparative analysis of six different models of ANN based on their characteristics, performance, and simulation time.…”
Section: Literature Review and Problem Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…In paper [ 12 ], the author used an artificial neural network to predict short-term load because of the non-linear characteristics of ANN compared to other statistical models such as ARMAX, ARMA, regression, and Kalman filtering. Using MATLAB, he did a comparative analysis of six different models of ANN based on their characteristics, performance, and simulation time.…”
Section: Literature Review and Problem Relevancementioning
confidence: 99%
“…Furthermore, by introducing a compensation factor in the load profile data, the performance outcomes have been further improved. Authors in [ 12 ] used ANN to perform load forecasts. They demonstrated that the radial basis neural network is the fastest and most accurate model of neural networks for load prediction.…”
Section: Literature Review and Problem Relevancementioning
confidence: 99%
“…These models correspond to artificial intelligence algorithms that perform better with non-linear data. Feedforward Multilayer Perceptron (MLP), Support Vector Regression (SVR) , LSTM, among others, are included in this group [8]. In [9], Tang and Zhang (2011) combines ANNs with the grey optimization model for load prediction.…”
Section: Traditional Load Prediction Methods Use Statistical Models mentioning
confidence: 99%
“…This optimization problem requires a dayahead hourly forecast of the load, generated power, and grid price. Even though load and energy generation forecasting is a difficult task [13], multiple works have proposed various approaches to forecasting with reasonable accuracy [14]- [17].…”
Section: Introductionmentioning
confidence: 99%